Measuring the Quality of the Institutional Environment through the Development of Prices of Credit Default Swaps in Times of Economic Disturbances - Steinhauser, Dušan, 1988-
Inštitucionalizmus, inštitúcie a transakčné náklady. Teória efektívnych trhov a kredity úverového zlyhania.